ONLINE LEARNING AND BLENDED LEARNING - Trubina Jasmin (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Over the past decade, enabled by educational and technological innovationss, teaching and learning in higher education has been suffering many changes, not only on instructional design and delivery but also on student advising and rating. Many promising practices have evolved to integrate the traditional learning with innovative means in order to create a new learning environment to maximize learning flexibility, enhance learning effectiveness and enrich learning experience. Blended learning, online learning and personalized learning are sample of these integrations.